Hole-doped room-temperature superconductivity in H3S1-xZx (Z=C, Si). (December 2020) - Ge, Yanfeng; Zhang, Fan; Dias, Ranga P.; Hemley, Russell J.; Yao, Yugui
Abstract: We examine the effects of the low-level substitution of S atoms by C and Si atoms on the superconductivity of H3 S with the I m 3 ¯ m structure at megabar pressures. The hole doping can fine-tune the Fermi energy to reach the electronic density-of-states peak maximizing the electron-phonon coupling. This can boost the critical temperature from the original 203 K to 289 K and 283 K, respectively, for H3 S0.962 C0.038 at 260 GPa and H3 S0.960 Si0.040 at 230 GPa. The former may provide an explanation for the recent experimental observation of room-temperature superconductivity in a highly compressed C–S–H system [Nature 586, 373–377 (2020)]. Our work opens a new avenue for substantially raising the critical temperatures of hydrogen-rich materials. Graphical abstract: Image 1 Highlights: Predicting room-temperature superconductivity in hole-doped H3 S system. Providing an explanation for the experimentally observed room-temperature superconductivity in a C–S–H system. Opening a new avenue for substantially raising the superconducting critical temperatures of hydrogen-rich materials.